Spinal cord injury without radiographic abnormalities caused by rotation-stretching injury manifesting as Brown-Sequard syndrome: a case report - Zhong, Wentao; Pu, Mengyang; Zhang, Yu; Zhang, Peng; Shen, Yixin (Journal of the Pakistan Medical Association, 2023)
Spinal cord injury without radiographic abnormality (SCIWORA) is a term that denotes clinical symptoms of traumatic myelopathy without radiographic or computed tomographic features of vertebral fracture or instability. However, SCIWORA in adults is very rare, especially that involving the thoracic spine. We describe the case of a 38-year-old man who complained of weakness in the right lower extremity for two hours. The injury occurred due to rapid spinal cord rotation-stretching. The patient was diagnosed with SCIWORA at the T4 level, manifesting as Brown-Sequard syndrome (BBS). Finally, he was able to walk independently without assistance after two-month treatment. SCIWORA due to spinal cord rotation-stretching injury, manifesting as BSS, is a very rare mechanism of injury. When X-ray and CT scans rule out the diagnosis of spinal fractures, SCIWORA should be suspected. —Continue